Tetrodotoxin abruptly blocks excitatory neurotransmission in mammalian CNS. (1st September 2015) - Wakita, Masahito; Kotani, Naoki; Akaike, Norio
Abstract: The present study utilised a 'synaptic bouton' preparation of mechanically isolated rat hippocampal CA3 pyramidal neurons, which permits direct physiological and pharmacological quantitative analyses at the excitatory and inhibitory single synapse level. Evoked excitatory and inhibitory postsynaptic currents (eEPSCs and eIPSCs) were generated by focal paired-pulse electrical stimulation of single boutons. The sensitivity of eEPSC to tetrodotoxin (TTX) was higher than that of the voltage-dependent Na + channel whole-cell current ( I Na ) in the postsynaptic CA3 soma membrane. The synaptic transmission was strongly inhibited by 3 nM TTX, at which concentration the I Na was hardly suppressed. The IC50 values of eEPSC and I Na for TTX were 2.8 and 37.9 nM, respectively, and complete inhibition was 3–10 nM for eEPSC and 1000 nM for I Na . On the other hand, both eEPSC and eIPSC were equally and gradually inhibited by decreasing the external Na + concentration ([Na]o ), which decreases the Na + gradient across the cell membrane. The results indicate that TTX at 3−10 nM could block most of voltage-dependent Na + channels on presynaptic nerve terminal, resulting in abruptly inhibition of action potential dependent excitatory neurotransmission. Highlights: TTX inhibited sodium current ( I Na ) on soma membrane in a dose-dependent manner. The IC50 of I Na was 37.9 nM. eEPSC was abruptly inhibited by a very low dose (3 nM) of TTX. eEPSC was approximately 10- to 100-fold more sensitive to TTX than I Na as measured by various synaptic parameters. eEPSC and eIPSC were equally inhibited by decreasing external Na + concentrations.